Targeting microglia polarization with Chinese herb-derived natural compounds for neuroprotection in ischemic stroke - Lu Yu; Yin Dong; Mincheng Li; Huifang Liu; Cuina Yan; Xiaoxian Li; Yuehua Gu; Liwei Wang; Chuan Xu; Jie Xu; Zhen Yuan; Ming Xia; et al. (Frontiers in Cell and Developmental Biology)
Given that ischemic stroke ranks as one of the most fatal diseases globally, it is imperative to develop clinically effective neuroprotective agents for stroke. Microglia serve as innate immune cells for maintaining brain homeostasis, and upon activation, they are well-known to be able to transform into two functional phenotypes, namely, the M1 and M2 types, which can convert each other and exert opposing effects on neurotoxicity and neuroprotection, respectively. Traditional Chinese medicine possesses a deep-rooted and profound history with rich theory in treating cerebrovascular disorders, and its natural compounds have been considered as promising adjunctive therapies. Recently, researchers have been devoting attention to the inflammation-suppressive properties of the compounds from Chinese herbs. These compounds are gradually emerging as adoptable therapeutic agents with wide application prospect for improving stroke outcomes, through regulating microglial polarization to attenuate neuroinflammation. Thereby, we reviewed the functions of microglial cells in inflammation and neuroprotection and explored the regulation of microglial activity by natural compounds to alleviate neuroinflammation and protect neural function after ischemic stroke. Collectively, using natural compounds to suppress the microglia-mediated detrimental inflammatory response, meanwhile enhancing their anti-inflammatory abilities to accelerate neuronal recovery, will be promising therapeutic approaches for ischemic stroke.